The cerebellum is causally involved in episodic memory under aging - Almeida, Armando (2023)
Episodic memory decline is a major signature of both normal and pathological aging. Many neural regions have been implicated in the processes subserving both episodic memory and typical aging decline. Here, we demonstrate that the cerebellum is causally involved episodic memory under aging. We show that a 12-day neurostimulation program delivered to the right cerebellum led to improvements in episodic memory performance under healthy aging that long outlast the stimulation period - healthy elderly individuals show episodic memory improvement both immediately after the intervention program and in a 4-month follow-up. These results demonstrate the causal relevance of the cerebellum in processes associated with long-term episodic memory, potentially highlighting its role in regulating and maintaining cognitive processing. Moreover, they point to the importance of non-pharmacological interventions that prevent or diminish cognitive decline in healthy aging.